KESIAPAN PRAKTEK LAPANGAN INDUSTRI MAHASISWA TEKNIK SIPIL FT-UNP DI DUNIA USAHA/DUNIA INDUSTRI (DU/DI) - Saberda Pendra; Indrati Kusumaningrum; Revian Body (Universitas Negeri Padang, 2018)
Abstract— The background of this research is because in following the ISP some students of Civil Engineering Department of FT-UNP experienced doubts and problems while in the industrial field, such as: students are less active and do not participate with what is happening in the field, lack of understanding how to read the picture, less understanding how to pay volume with software. This study aims to reveal about the readiness of students of civil engineering department of UNP faculty of technical period from January to June 2017. This quantitative descriptive research with a population of 51 students in civil engineering State University Of Padang that implement Industry field experience (ISP) of the year 2017. The sample in this study as many as 34 students with sampling using simple random sampling technique. Data collected by questionnaire, with 5 categories of readiness ranging from: unprepared, poorly prepared, adequately prepared, prepared, and well prepared. Results of the research, got data of readiness of the students of Department of Civil Engineering faculty of Engineering State University of Padang in implementing the ISP is in ready category for affective aspects, cognitive aspect and psychomotor aspects. Viewed from the overall aspect that the readiness of field practice on Civil Engineering students FT-UNP in implementing ISP in Padang City in the ready category. Keywords: Readiness, ISP, The world of Business/Industry.